2023
DOI: 10.35848/1347-4065/acbc28
|View full text |Cite
|
Sign up to set email alerts
|

Ni/Au contacts to corundum α-Ga2O3

Abstract: The structural, chemical and electrical properties of Ni/Au contacts to atomic layer deposited α-Ga2O3 were investigated. Ni forms a Schottky contact with α-Ga2O3, irrespectively of the post-annealing temperature. No sign of metal oxidation was observed at the metal-semiconductor interface (unlike what is observed for other metals like Ti), and instead, the metallurgical processes of the Ni-Au bilayer dominate the electrical properties. It is found that 400-450oC is the optimal annealing temperature, which all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Although we cannot elaborate it quantitively, the ALD temperature does not have a significant impact on the Schottky contact, as observed from electrical characteristics at a low drain bias. It is reported that interdiffusion is marginal under an annealing temperature of 400 °C and that the Ni content was only 5% in the Ni-Au alloy [ 34 ]. The Ohmic contact exhibits a relatively mixed interface due to the formation of a Ti-Al inter-metallic phase, and oxygen vacancies facilitated the Ohmic contact by reducing contact resistance [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although we cannot elaborate it quantitively, the ALD temperature does not have a significant impact on the Schottky contact, as observed from electrical characteristics at a low drain bias. It is reported that interdiffusion is marginal under an annealing temperature of 400 °C and that the Ni content was only 5% in the Ni-Au alloy [ 34 ]. The Ohmic contact exhibits a relatively mixed interface due to the formation of a Ti-Al inter-metallic phase, and oxygen vacancies facilitated the Ohmic contact by reducing contact resistance [ 35 ].…”
Section: Resultsmentioning
confidence: 99%